2020
DOI: 10.1108/hff-10-2019-0732
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-Ag/blood hybrid nanofluid flow through an artery with applications of drug delivery and blood circulation in the respiratory system

Abstract: Purpose As transferring biological fluid through an artery is nowadays a pivotal subject, the purpose of this paper is to study the mathematical model of hybrid nanofluid flow comprising pure blood as base fluid and TiO2 and Ag as nanoparticles through the porous channel, which can be an applicable model for drug delivery. Design/methodology/approach Both walls of the channel have different permeability, which enables the fluid to enter and exit, and variable height, which dilates and squeezes at the uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(29 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Ellahi et al [28] conducted a numerical investigation of the peristaltic flow of couple stress-based gold nanofluid among the hole of dual co-axial cylinders with various outlines and structure. Chahregh and Dinarvand [29] examined the circulation of 2 TiO Ag  /blood, hybrid nanofluid across a vessel for blood as well as drug transport applications in the respiration process. Also, to the best of authors knowledge in the relevant literature, no one has ever tried to investigate the movement around a rotating sphere using pure blood as a based liquid and hybrid nanomaterials to explain many real-life applications of biomedical and medication filed and transportation.…”
Section: Aumentioning
confidence: 99%
“…Ellahi et al [28] conducted a numerical investigation of the peristaltic flow of couple stress-based gold nanofluid among the hole of dual co-axial cylinders with various outlines and structure. Chahregh and Dinarvand [29] examined the circulation of 2 TiO Ag  /blood, hybrid nanofluid across a vessel for blood as well as drug transport applications in the respiration process. Also, to the best of authors knowledge in the relevant literature, no one has ever tried to investigate the movement around a rotating sphere using pure blood as a based liquid and hybrid nanomaterials to explain many real-life applications of biomedical and medication filed and transportation.…”
Section: Aumentioning
confidence: 99%
“…Synthetic hybrid nanomaterials exhibit remarkable physicochemical properties that do not exist in the individual components (Sarkar et al, 2015). The studies (Ghadikolaei et al, 2017;Yousefi et al, 2018;Dinarvand, 2019;Shojaie Chahregh and Dinarvand, 2020;Ijaz et al, 2018) showed a promising reaction of hybrid nanofluids in heat transfer system, as its thermophysical properties produced a great tendency towards improved heat rate as compared to single nanoparticles. Because hybrid nanofluids showed a promising impact in a heat transfer system, there are still many studies carried out to study the stability and side effects of its implementation in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dinarvand et al (2019a) studied a new mass-based approach to a one-phase hybridity model considering TiO 2 -CuO/water hybrid nanofluid flow over a static/moving wedge or corner. After a while, Dinarvand et al (2019b), conducted a numerical study to improve the drug delivery micro-circulatory system in MHD hybrid CuO-Cu/blood nanofluid flow toward a porous stretching sheet, followed by Chahregh and Dinarvand (2020) who investigated the transferring biological fluid, i.e. TiO 2 -Ag/blood hybrid nanofluid through an artery by considering porous channel with applications of drug delivery and blood circulation in the respiratory system.…”
Section: Introductionmentioning
confidence: 99%